Hukum Islam dan Kebebasan Pers di Indonesia Studi terhadap Fatwa MUI tentang Jurnalisme Islami - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Mutia Hibatul Hamdah; Alima Najah; Dihni Khalisa Rachman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Freedom of the press is a fundamental part of a democratic system, including in Indonesia. However, in a society that is predominantly Muslim, there are challenges in balancing freedom of the press with Islamic values. One form of Islamic influence on the world of journalism in Indonesia is the fatwa of the Indonesian Ulema Council (MUI) on Islamic journalism. This study aims to analyze how the fatwa regulates journalistic practices, the extent of its influence on press freedom, and the challenges that arise in its implementation. This study uses a qualitative approach with a document analysis method, including a study of the MUI fatwa, press regulations in Indonesia, and related literature. The results of the study show that the MUI fatwa emphasizes the principles of honesty, moral responsibility, and compliance with Islamic teachings in journalistic practice. This fatwa encourages Muslim journalists to present news that is not only accurate but also in accordance with religious norms. Although it does not have binding legal force, this fatwa still has a major influence, especially for Islamic-based media and Muslim journalists. However, this study also found the potential for conflict between the principle of press freedom which prioritizes independence and the principle of Islamic journalism which demands limitations according to religious norms. Therefore, dialogue is needed between stakeholders, such as the MUI, the press, and the government, in order to find a balance between press freedom and Islamic values ​​in journalistic practices in Indonesia.